NETWORKING 2010 9th International IFIP TC 6 Networking Conference, Chennai, India, May 11-15, 2010. Proceedings - Crovella, Mark.; Feeney, Laura Marie; Rubenstein, Dan.; Raghavan, S. V.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the refereed proceedings of the 9th IFIP-TC6 Networking Conference, Networking 2010. Papers were solicited in three broad topic areas: applications and services, network technologies, and internet design. All papers were considered on their merits by a uni?ed Technical ProgramCommittee (TPC); there was no attempt to enforce a quota among topic areas. We believe the resulting program is an excellentrepresentationofthebreadthofrecentadvancesinnetworkingresearch. This year, the conference received 101 full paper submissions from 23 co- trieson?vecontinents,re?ectingastrongdiversityinthenetworkingcommunity. Similarly, the 92 members of the TPC are from 21 countries and include a mix of academic, industry, and governmental a?liations. The TPC members, aided by some 50 external reviewers, provided a total of 470 reviews and follow-up discussions totaling more than 200 messages. The ?nal selections were made at a TPC meeting hosted by Columbia University in New York City, with both in-person and remote participation. In total, authors of accepted papers have academic and industry a?liations in 15 countries. We ?nally selected 24papers for presentationduring the conference technical sessions. A small number of papers were assigned a shepherd from the TPC to assist in paper revision. These statistics represent an acceptance rate of just under 24%, comparable to that of previous years. The TPC also identi?ed several papers that re?ect particularly promising early results; these papers were selected for presentation as work-in-progress papers and are identi?ed as such in the proceedings.
P2P and Overlay Networks -- Using Torrent Inflation to Efficiently Serve the Long Tail in Peer-Assisted Content Delivery Systems -- Network Distance Prediction Based on Decentralized Matrix Factorization -- Topology-Awareness and Reoptimization Mechanism for Virtual Network Embedding -- Survivable Virtual Network Embedding -- Toward Efficient On-Demand Streaming with BitTorrent -- Synapse: A Scalable Protocol for Interconnecting Heterogeneous Overlay Networks -- Performance Measurement -- A Longitudinal Study of Small-Time Scaling Behavior of Internet Traffic -- Measurement Study of Multi-party Video Conferencing -- Quality of Service -- Passive Online RTT Estimation for Flow-Aware Routers Using One-Way Traffic -- A Flow Scheduler Architecture -- Stateless RD Network Services -- Wireless Networks -- Multicast in Multi-channel Wireless Mesh Networks -- Ambient Interference Effects in Wi-Fi Networks -- A Zone Assignment Algorithm for Fractional Frequency Reuse in Mobile WiMAX Networks -- Addressing and Routing -- Handling Transient Link Failures Using Alternate Next Hop Counters -- Efficient Recovery from False State in Distributed Routing Algorithms -- IP Fast Reroute in Networks with Shared Risk Links -- EAU: Efficient Address Updating for Seamless Handover in Multi-homed Mobile Environments -- Applications and Services -- Speculative Validation of Web Objects for Further Reducing the User-Perceived Latency -- Dynamic Service Placement in Shared Service Hosting Infrastructures -- Evaluating the Impact of a Novel Warning Message Dissemination Scheme for VANETs Using Real City Maps -- Ad Hoc and Sensor Networks -- Resource Optimization Algorithm for Sparse Time-Driven Sensor Networks -- Routing Protocol for Anycast Communications in a Wireless Sensor Network -- Fault-Tolerant Power-Aware Topology Control for Ad-Hoc Wireless Networks -- Work in Progress -- Server Guaranteed Cap: An Incentive Mechanism for Maximizing Streaming Quality in Heterogeneous Overlays -- End-to-End Throughput with Cooperative Communication in Multi-channel Wireless Networks -- Cost Bounds of Multicast Light-Trees in WDM Networks -- Bidirectional Range Extension for TCAM-Based Packet Classification -- Estimating the Economic Value of Flexibility in Access Network Unbundling -- Intercarrier Compensation between Providers of Different Layers: Advantages of Transmission Initiator Determination -- Application of Secondary Information for Misbehavior Detection in VANETs -- Path Attestation Scheme to Avert DDoS Flood Attacks.
Keywords: Computer science; Computer communication systems; Software engineering; Data encryption (Computer science).; Algorithms; Management information systems; Computer Science; Computer Communication Networks; Software Engineering/Programming and Operating Systems; Information Systems Applications (incl. Internet).; Algorithm Analysis and Problem Complexity; Management of Computing and Information Systems; Data Encryption; Electronic books